PENGARUH PENAMBAHAN SERAT POLYPROPYLENE PADA BETONRINGAN DENGAN TEKNOLOGI FOAM TERHADAP KUAT TEKAN, KUAT TARIK BELAH DAN MODULUS ELASTISITAS - Purnawan Gunawan; Wibowo Wibowo; Nurmantian Suryawan (Program Studi Teknik Sipil FT UNS, 2014)
The density of concrete is one of aspect which is calculated when planning a building framework because it influencing the weighting calculation. Forthat reason, there are many kinds of research on the lightweight concrete and one of them is making a lightweight concrete using foam technology.Foam lightweight concrete is made by adding foam agent which consist of spectafoam, harder mild, and polymer into a mortar mix. Nowadays, theusing of lightweight concrete still directed only to a non-structural concrete because generally a lightweight concrete has maximum compressivestrength at 15 MPa. The solution to improve this foam lightweight concrete's strength is by adding fiber to the mixing in form of polypropylene Themethod used was experimental observations and theoretical analysis then performed to support the conclusion eventually. The specimen is in form ofcylinder with diameter of 15 cm and height of 30 cm for testing the modulus of elacity, compressive strength, and the split tensile strength. Thisexperiment using CTM (Compression Testing Machine) tool. The result of the research is the increase of the value of foam lightweight concrete'scompressive strength, split tensile strength, and modulus of elasticity on the polypropylene fiber addition rate of 0.75% from the concrete's volumeweight. Fiber additional rate of 0.75% resulting the increase of compressive strength, split tensile strength, and the modulus of elasticityconsecutively 27.93%; 60.38%; and 44.31% compared to the foam lightweight concrete which has no fiber.